Removal of PPCPs from the sludge supernatant in a one stage nitritation/anammox process. (1st January 2015) - Alvarino, T.; Suarez, S.; Katsou, E.; Vazquez-Padin, J.; Lema, J.M.; Omil, F.
Abstract: Pharmaceutical and personal care products (PPCPs) are extensively used and can therefore find their way into surface, groundwater and municipal and industrial effluents. In this work, the occurrence, fate and removal mechanisms of 19 selected PPCPs was investigated in an 'ELiminación Autótrofa de Nitrógeno' (ELAN ® ) reactor of 200 L. In this configuration, ammonium oxidation to nitrite and the anoxic ammonium oxidation (anammox)processes occur simultaneously in a single-stage reactor under oxygen limited conditions. The ELAN ® process achieved high removal (>80%) of the studied hormones, naproxen, ibuprofen, bisphenol A and celestolide, while it was not effective in the removal of carbamazepine (<7%), diazepam (<7%) and fluoxetine (<30%). Biodegradation was the dominant removal mechanism, while sorption was only observed for musk fragrances, fluoxetine and triclosan. The sorption was strongly dependent on the granule size, with smaller granules facilitating the sorption of the target compounds. Increased hydraulic retention time enhanced the intramolecular diffusion of the PPCPs into the granules, and thus increased the solid phase concentration. The increase of nitritation rate favored the removal of ibuprofen, bisphenol A and triclosan, while the removal of erythromycin was strongly correlated to the anammox reaction rate. Graphical abstract: Highlights: Biodegradation is the dominant removal mechanism for PPCPs. Sorption is dependent on the biomass particle size and contact time. HRT affects the removal of lipophilic compounds. Increase of nitritation rate favors the removal of ibuprofen, bisphenol A, triclosan. Anammox activity is strongly correlated to the removal of erythromycin.